Development of a fiber optic gradient hydrophone - Mei, Suo Hai. (2008)
Fiber optic hydrophones have been under development since 1970s, and have been proven to have many advantages over their traditional counterparts, such as PZT hydrophones. Efforts have been made in increasing its sensitivity and dynamic range and in sensor packaging. Some attempts have also been made in the construction of pressure gradient sensors, however this area has not been intensively investigated so far.